MARKETING IN MEDICINE AND ITS CHARACTERISTICS - Muyassarova Muxabbat Muxammadievna (Scholar Express Journals, 2023)
This article explores the dynamic intersection of marketing and medicine, shedding light on the unique characteristics that define this evolving field. As the healthcare landscape undergoes unprecedented changes, the role of marketing in medicine has become increasingly prominent. This study delves into the multifaceted nature of medical marketing, examining its strategic importance, ethical considerations, and the impact of digitalization on patient engagement. Through a comprehensive analysis, the article aims to provide insights into the challenges and opportunities inherent in marketing within the medical realm, offering valuable perspectives for healthcare professionals, marketers, and policymakers alike.
Keywords: Medical Marketing; Healthcare Communication; Strategic Healthcare Management; Healthcare Branding